PENGARUH WAKTU STABILISASI PADA SEQUENCING BATCH REACTOR AEROB TERHADAP PENURUNAN KARBON - Sumiyati, Sri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
One  of  biological  wastewater  treatment  process    modification  Sequencing  Batch  Reactor by exploiting  period  of  stabilization  time  earn  to  lessen  capacities  of  total  aeration volume. Mechanism  that  happened  in  this  SBR  modification  same  as  that  happened  in Contact Stabilization.  There  was  existence  process  biosorption,  was  due  to  adsorption  of  the organic matter  onto  sludge  particels,  during  the  contact  period  (fill  -  react  time).This  research aim  to know  influence  of  stabilization  time  to  degradation  of  COD.  This  research,  used  SBR reactor with volume operate for 5 Liter with COD influent consentration 1139.2 mg/L. The variation of stabilization  time  :  3,  4,  5  and  6  hours  and  time  reacted  :  0,5  ;  1  ;  1,5  and  2  hours as independent  variables.  COD  effluent  concentration  as  depended  variable.Result  of research indicate that progressively time of stabilization and concentration COD (mg/L) will experience of efficiency  improvement.  Time  reacted  to  give  influence  the  happening  of  biosorption (the adsorption of organic matter onto sludge particel). The fenomena that happened is degradation of concentration COD will achieve maximum level at the total contact time 1,5 hour. Efficiency of optimum degradation COD become of variation  r/s = 1 : 6.